Vaccinate-assess-move method of mass canine rabies vaccination utilising mobile technology data collection in Ranchi, India. Issue 1 (December 2015) - Gibson, Andrew; Ohal, Praveen; Shervell, Kate; Handel, Ian; Bronsvoort, Barend; Mellanby, Richard; Gamble, Luke
Abstract Background Over 20 000 people die from rabies each year in India. At least 95 % of people contract rabies from an infected dog. Annual vaccination of over 70 % of the dog population has eliminated both canine and human rabies in many countries. Despite having the highest burden of rabies in the world, there have been very few studies which have reported the successful, large scale vaccination of dogs in India. Furthermore, many Indian canine rabies vaccination programmes have not achieved high vaccine coverage. Methods In this study, we utilised a catch-vaccinate-release approach in a canine rabies vaccination programme in 18 wards in Ranchi, India. Following vaccination, surveys of the number of marked, vaccinated and unmarked, unvaccinated dogs were undertaken. A bespoke smartphone 'Mission Rabies' application was developed to facilitate data entry and team management. This enabled GPS capture of the location of all vaccinated dogs and dogs sighted on post vaccination surveys. In areas where coverage was below 70 %, catching teams were re-deployed to vaccinate more dogs followed by repeat survey. Results During the initial vaccination cycle, 6593 dogs were vaccinated. Vaccination coverage was over 70 % in 14 of the 18 wards. A second cycle of vaccination was performed in the 4 wards where initial vaccination coverage was below 70 %. Following this second round of vaccination, coverage was reassessed and found to be over 70 % in two wards and only just below 70 % in the final two wards (66.7 % and 68.2 %, respectively). Conclusion Our study demonstrated that mobile technology enabled efficient team management and rapid data entry and analysis. The vaccination approach outlined in this study has the potential to facilitate the rapid vaccination of large numbers of dogs at a high coverage in free roaming dog populations in India.